2020
DOI: 10.1111/plb.13079
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of acetylcholine in chlorophyll metabolism and photosynthetic gas exchange in Nicotiana benthamiana seedlings under salinity stress

Abstract: Acetylcholine (ACh) is believed to improve plant growth. However, regulation at biochemical and molecular levels is largely unknown.• The present study investigated the impact of exogenously applied ACh (10 µM) on growth and chlorophyll metabolism in hydroponically grown Nicotiana benthamiana under salt stress (150 mM NaCl).• Salinity reduced root hydraulic conductivity while ACh-treated seedlings exhibited a significant increase, resulting in increased relative water content. Salinity induced a reduction in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 60 publications
(62 reference statements)
2
29
0
Order By: Relevance
“…In the same way, Pn, gs, E, and PSII activity was enhanced due to MYO exogenous application and amendment of the saline regime. Similarly to our results, a decline in chlorophyll content, Pn, gs, E, and PSII activity has been reported in different plants [7,[75][76][77]. In salt-stressed Dianthus caryophyllus, Kwon et al [74] demonstrated a decline in Pn, gs, E, intercellular CO 2 , and stomata cavity in the lower and upper epidermis, with a significant decrease in their size and density.…”
Section: Discussionsupporting
confidence: 89%
“…In the same way, Pn, gs, E, and PSII activity was enhanced due to MYO exogenous application and amendment of the saline regime. Similarly to our results, a decline in chlorophyll content, Pn, gs, E, and PSII activity has been reported in different plants [7,[75][76][77]. In salt-stressed Dianthus caryophyllus, Kwon et al [74] demonstrated a decline in Pn, gs, E, intercellular CO 2 , and stomata cavity in the lower and upper epidermis, with a significant decrease in their size and density.…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, when plants are subjected to salinity, stomatal guard cells limit stomatal conductance to reduce the transpiration rate, consequently impairing the photosynthesis and gas exchange parameters [33] (Figure 2). Indeed, the photosynthesis system is reported as one of the first physiological processes affected by saline stress, and Qin et al [8] reported a direct correlation between the amelioration of gas exchange parameters, affected by salinity, and the recovery of photosynthesis activity, after the exogenous application of acetylcholine (ACh). The authors confirmed that salt stress produced a reduction in chlorophyll biosynthetic intermediates, i.e., protoporphyrin-IX, Mg-photoporphyrin-IX, and protochlorophyllide, which were significantly enhanced in the presence of ACh.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some authors reported that the regulation of chlorophyll biosynthesis in plants depends on the type of stress applied, producing important consequences on the growth and reduction of biomass [5][6][7]. To overcome salinity-mediated growth reduction, plants activate tolerance mechanisms such as antioxidant systems, osmolyte accumulation, and the compartmentalization of toxic ions [8]. Many studies have previously shown that the production and accumulation of reactive oxygen species (ROS) such as superoxide (O 2 − ), hydrogen peroxide (H 2 O 2 ), and singlet oxygen are parallel with exposure time and density in plants exposed to salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of PChlide is considered to be the rate-limiting step of the chlorophyll branch and as the rate of Chl protein synthesis depends strictly on Chl availability. Moreover, the shortage and excess of por enzyme activity will have a fatal effect on cell activity ( Qin et al, 2020 ). Other pigments such as chlorophyll b and carotenoids absorb light energy and transfer to chlorophyll a ( Rai et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%